Analis Risiko Produksi Komoditas Melon Hidroponik di PT Turrima Agro Mass Kecamatan Gemolong Kabupaten Sragen - Ghassani, Farhan; Setiyawan, Hery; Handayani, Migie (Universitas Galuh, 2025)
Melon production at PT Turrima Agro Mass fluctuates. This condition causes losses, the company needs to handle the risks that occur. This study aims to analyze the risk of melon production, risk events and agents and strategies for handling melon production risks. This study was conducted in November 2024, at PT Turrima Agro Mass, Sragen Regency. The location was determined purposively with the consideration that the company is engaged in agriculture and is located in an area that has horticultural crop production, one of the superior commodities of which is hydroponic melon. The research method used is a case study. The sample collection method uses purposive respondents consisting of 14 people as key informants. Data collection techniques are observation and interviews. Data analysis uses the Coefficient of Variation (CV) and the House of Risk (HOR) method. The results of the study are that the risk level at PT Turrima Agro Mass is classified as high with a CV of 19.17%. HOR Phase 1 identified 14 risk events and identified 14 risk sources. The priority sources of risk obtained are increased pests and diseases, extreme weather changes, leaves and stems attacked by pests and diseases, and suboptimal handling of pests and diseases. The risk management strategy obtained 7 strategies, namely the implementation of the Integrated Pest and Disease Control (PHPT) system, following weather developments and preparing mitigation, improving the quality of the workforce, optimizing melon land sanitation, determining the planting calendar according to weather and climate patterns, collaboration and exchange of information, selecting quality seeds.